Territorialidades rurais em Júlio de Castilhos RS: da pecuária extensiva à agricultura familiar. - Moreira, Vinicius Silva (2008)
Júlio de Castilhos City has undergone significant transformations in its rural space last decades. It has happened because of large lands retraction and extensive cattle ranching in favour of Soya new agriculture. The partial fragmentation of cattle breeding and its reorganization has occurred in three main forms: land rent, land sell and expropriation when non-productive land. It was carried out by Instituto Nacional de Colonização e Reforma Agrária (INCRA) because they were not taking their social function. The rural settlements made possible the introduction and the development of family farm in Júlio de Castilhos City and consequently the diversification of agricultural production. This research aimed at understanding the processes held responsible for the dynamics of Júlio de Castilhos rural space and its resulting conflits from 1960 to 2007. Moreover, it was analyzed productive, landing and socioeconomic transformations responsible for the formation of rural lands. The methodology is analytical and descriptive, based on field researches, through observation and interviews with farmers, landowners and other qualified informants.